Políticas públicas da educação e da saúde na Maternidade Escola Assis Chateaubriand da Universidade Federal do Ceará: a percepção dos atuais gestores - Xenofonte, Maria Isomar da Silva (2010)
The economic and institutional space that involves the health sector has been go through deep transformations in Brazil, lazily following the tendency of developed countries, in cultural and historic conditions and, thus, structural specifics enough. In Brazil, the health sector adjustment ways are on their earlier stages of conception and application. The university hospitals, even characterized as school-hospitals can’t find an escape from these protections, once they need resources to keep working. Today they live in the middle of financial and management crises: there aren’t human and materials resources and hospital beds. About the Federal University of Ceará case, with two school-hospitals, with the, University Hospital Walter Cantídio and the other Maternity School Assis Chateaubriand, the situation doesn’t seem to be different. This hospital complex, currently, is going through a restructuring process since 2009, trying to find alternatives to enable, in an expressive way, the accomplishment of its mission and its social function. Before this context, a selection was made on the critique’s horizon and it was tried to answer this question: the Maternity School Assis Chateaubriand has been accomplished its social function according the Health and Education State Department’s public politics execution, making sure the indispensable conditions, the hospital assistance humanized, with quality concerning the mother-child binomial and, at the same time, articulating instruction, research and extension on the graduation and post graduation? By this way, the principal objective of this study is identify the real possibilities of the execution of the health and instruction public politics at the MEAC quotidian in theirs social author vision. This study is inserted on the qualitative approach research with the technical modality of the case study and adopted as references the institutional management written reports between the years 2003 and 2009 and questionnaires about the instruction and health public politician accomplishment on MEAC were applied. As the respondent of the research, were twenty components as manager professors and administrative-technicists from MEAC. In part, the data showed compliance with the policies of education and health in the MEAC, grounded in strategic planning and participatory management, despite marked also by some deficiencies to be corrected in future management plans.